SARS-CoV-2 Molecular Evolutionary Dynamics in the Greater Accra Region, Ghana - Bright Adu; Joseph H.K. Bonney; Beverly Egyir; Isaac Darko Otchere; Prince Asare; Francis E. Dennis; Evelyn Yayra Bonney; Richard Akuffo; Ivy A. Asante; Evangeline Obodai; Selassie Kumordjie; Joyce Appiah-Kubi; et al. (Emerging Infectious Diseases, 2023)
To assess dynamics of SARS-CoV-2 in Greater Accra Region, Ghana, we analyzed SARS-CoV-2 genomic sequences from persons in the community and returning from international travel. The Accra Metropolitan District was a major origin of virus spread to other districts and should be a primary focus for interventions against future infectious disease outbreaks.